VD_FINDINFO ML / 2020 / 203 vom 20. August 2020 - VD Tribunal cantonal (2020)
RESTITUTION DU DÉLAI, MEILLEURE FORTUNE, DROIT D'ÊTRE ENTENDU, VICE DE FORME | 29 al. 2 Cst., 132 al. 1 CPC (CH), 148 al. 1 CPC